ANALISIS RASIO KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PT INDOCEMENT TUNGGAL PRAKARSA TBK - Rosyidatul Maulidinah; Gideon Setyo Budiwitjaksono (Jurnal Proaksi, 2021)
Indonesia as a developing country always carries out infrastructure development with this development as well as increasing cement production as one of the products needed. For this reason, the company PT Indocement Tunggal Prakarsa TBK needs to conduct financial ratio analysis with the aim of measuring financial performance and as an indicator of changes in the company's financial conditions. Research using quantitative descriptive methods in measuring the financial performance of PT Indocement Tunggal Prakarsa TBK 2015-2019 with the ratio of liquidity, solvency, activity, and profitability. The data collection technique is documentation with secondary data. With the result that the liquidity and solvency ratios show liquid and optimal results, while the activity and profitability ratios are less than optimal. Keywords: Financial Performance, Financial Ratio, Ratio Analysis